Implementasi Metode Role Playing Dalam Pembelajaran Bahasa Arab Pada Aspek Berbicara - Dewi Ferawati; Nurhidayah (Tarbiya Islamica, 2023)
The Role Playing learning method is a method that can be applied in the learning process in the classroom because this model is attractive to students. The purpose of this study was to describe and analyze the planning of the role playing method in learning Arabic in terms of speaking; 2) describe and analyze the implementation of the role playing method in learning Arabic on the speaking aspect and describe and analyze the evaluation of the role playing method in learning Arabic on the speaking aspect at MIS Bina Dharma Parit Wednesday. This study uses a qualitative approach and a case study type of research. Data collection techniques using interviews, observation, and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Research result; planning for the role playing method in learning Arabic in the aspect of speaking at MIS Bina Dharma Parit Rabu is carried out in the following way: a) Preparing a learning syllabus, b) preparing an RPP (Learning Implementation Plan), c) compiling assessment instruments, d) dividing roles before implementation of learning. The implementation of the role playing method in learning Arabic in the aspect of speaking at MIS Bina Dharma Parit Rabu, namely: a) warming up, b) setting the stage, c) appointing several students as observers, d) starting the role playing game, e) discussing the game , f) discussing discussion and evaluation. (3) Evaluation of the role playing method in learning Arabic on the speaking aspect at MIS Bina Dharma Parit Wednesday 2, namely: a) process evaluation, b) outcome evaluation.